INNOVATIVE TECHNOLOGIES AND EDUCATION - Pardabayeva Muqaddas Mirzamurod’s daughter (Sciental Journals Publishing, 2025)
This article highlights the essence and role and importance of the use of innovative pedagogical technologies in education in improving the quality of Education. Also, this article reflects on the effect of the application of innovative pedagogical technologies in the educational process and offers proposals for a new approach to the educational process in higher educational institutions.
Keywords: Innovation, pedagogical technology, quality of education, IT specialists, innovative approach.